Integration of Islamic Spiritual Values in Tazkiyatun Nafs for the Recovery of Narcotic Addiction Clients - Wahyu Adytia Wardana (Al-Wa'iyah, 2025)
Drug abuse in Indonesia continues to increase every year, demanding a more holistic rehabilitation approach. Conventional models focusing only on medical and psychological aspects are often unable to provide comprehensive recovery. This study aims to analyze the integration of Islamic spiritual values in the recovery process of addiction clients at Baitu Syifa Rehabilitation Center, Deli Serdang. A qualitative approach was used through observation, in-depth interviews with counselors, medical staff, and clients, as well as documentation during the period January–March 2025. The findings reveal that the integration of Islamic spirituality is manifested through activities such as dhikr, congregational prayer, Qur’anic recitation, Tahsin, and spiritual guidance based on the concept of tazkiyah an-nafs. These practices strengthen self-awareness, foster behavioral control, and cultivate new meaning in life for post-rehabilitation clients. The Islamic spiritual approach has proven to accelerate recovery and prevent relapse by building a vertical connection between clients and their Creator. This research confirms that Islamic spirituality is not merely supplementary but a central component in a sustainable and holistic rehabilitation model.